Phytochemical analysis of the leaves of Chromolaena odorata (Asteraceae) / Nuha Che Man - Che Man, Nuha (Faculty of Applied Sciences, 2010)
Chromolaena odorata is a species from family of Asteraceae. Most of the phytochemical surveys carried out on in this family were concentrated on the testing on flavonoids since flavonoids were generally proven to be effective as therapeutically agents. Not only that, other compounds present in the plant also have been studies. Therefore a study on chemical constituents of the stem of Chromolaena odorata (500g) was conducted. The crude extracts were obtained by extraction by using hexane and methanol. The crude extract obtained from dichloromethane is 3.88g, isolation works were carried out using various chromatographic techniques. That result in a mixture of the compounds was founds. These mixtures known as 4’, 5-dihydroxy-3, 7-dimethoxyflavone and another are types of flavonone. These structures are identified based on spectroscopic analysis using 1H NMR, 13C NMR, APT, HMQC Nuclear Magnetic Resonance (NMR)